2014
DOI: 10.1155/2014/720385
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Intraocular Pressure of Switching from Latanoprost and Travoprost Monotherapy to Timolol Fixed Combinations in Patients with Normal-Tension Glaucoma

Abstract: Purpose. To evaluate the effect on intraocular pressure (IOP) of switching from latanoprost and travoprost monotherapy to timolol fixed combinations in Japanese patients with normal-tension glaucoma (NTG). Methods. 27 NTG patients (54 eyes) were compared IOP, superficial punctuate keratitis (SPK) scores, and conjunctival injection scores in eyes treated with prostaglandin (PG) or PG analog/beta-blocker (PG/b) fixed-combination 6 months after the change in therapy. Results. The mean baseline intraocular pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(18 reference statements)
1
1
0
1
Order By: Relevance
“…PGA therapy reduced IOP by more than 20% from pretreatment values even in patients with NTG [ 24 , 25 ]. The 10% reduction observed in this study after switching to Duotrav is similar to those reported previously in NTG populations [ 26 , 27 ]. The absolute reduction of about 1.5 mmHg associated with switching to Duotrav seems to represent a meaningful treatment benefit, considering the findings from the Early Manifest Glaucoma Trial where every 1 mmHg of IOP reduction has patient benefit [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…PGA therapy reduced IOP by more than 20% from pretreatment values even in patients with NTG [ 24 , 25 ]. The 10% reduction observed in this study after switching to Duotrav is similar to those reported previously in NTG populations [ 26 , 27 ]. The absolute reduction of about 1.5 mmHg associated with switching to Duotrav seems to represent a meaningful treatment benefit, considering the findings from the Early Manifest Glaucoma Trial where every 1 mmHg of IOP reduction has patient benefit [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…Since 1996, latanoprost has been approved for clinical use in the United States and Europe and was introduced as the first prostaglandin analog in Korea. In Japan, prostaglandin analogs have become the first-line treatment for NTG because of their ability to reduce IOP [ 5 ]. As in Japan, a survey of the Korean Glaucoma Society resulted in agreement that the first-line treatment for NTG is a prostaglandin analog, especially latanoprost.…”
Section: Introductionmentioning
confidence: 99%
“…В метаанализе Aptel F. et al (2012) ФК латанопрост/тимолол (ФКЛТ) оказывала более выраженное гипотензивное действие в сравнении с монотерапией латанопростом, подтвержден меньший риск развития НЯ [15]. Аналогичные результаты получены Igarashi R. et al (2014) [16].…”
Section: результаты клинических исследованийunclassified